Expanding opportunities for the entrepreneurial poor a strategic plan for the Federation of People's Sustainable Development Cooperative (FPSDC) - Queipo, Karl Vincent M.; Soledad, Miguel D.; Concepcion, Sylvia B. (Davao City School of Management, University of the Philippines Mindanao, 2006)
Credit is traditionally provided by formal financial institutions like banks and finance companies. However, set against the poverty backdrop of the Philippines, credit may also be from non-traditional sources. In the communities where marginal sectors are labelled as ?unbankable? , credit is often supplied by money-lenders and more recently by cooperatives and non-government organizations. One of the programs developed and proven to be effective is micro-finance. However, difficult challenges encountered by the different Financing Cooperatives to provide micro-finance services often led to its closure or often created negative impression to the marginalized communities. The Federation of Peoples Sustainable Development Cooperative is currently facing a challenge of the same nature. The Federation of Peoples Sustainable Development Cooperative (FPSDC) started as a Central Loan Fund (CLF) Program of the Philippine Development Assistance Programme (PDAP) Inc. a Canadian ?Official Development Assistance (ODA) Programme in the Philippines for poverty alleviation and food security in the rural communities in 1994. In 1997, FPSDC has evolved from a program with the rural poor as clients to a federation with members as partners. By 1998, the CLF revolving grant fund of about Php 32 million has supported over 4,000 households involving 24 Non-Government Organizations (NGO?s) and Peoples Organizations (PO?s) and covering 49 grassroots project. The study involves key informant interview and focus group discussions to gather information regarding issues and concerns of FPSDC. The key individuals are selected from different stakeholder that has been in close partnership status with FPSDC individually or institutionally. Secondary data are gathered from books, publications, and internet research to provide additional information needed for the analysis. The simple yet comprehensive strategic management model of Fred David provided an easy tool in the logical flow of the external and internal analysis, towards the strategic option up to strategic measures. The strategic management study of FPSDC is intended to be a short, concise and yet specific paper to help resolve strategic issues in the next five years. The paper analyzes the past operations and challenges that will be faced by FPSDC. The main problem identified by the study was the lean staffing of the cooperative with a nationwide reach. Another is the absence of a comprehensive marketing strategy. The main recommendation of the study was to develop an efficient collection system and to expand membership in order to increase savings mobilization and decrease provision for bad loans.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, April 2006
Keywords: Strategic plan